International Symposium on Composers of African & Afro-Caribbean Descent: Veni, Vidi, Vici - Shaw, Paul (International Journal of Bahamian Studies, 2013)
Sharing a history similar to its Caribbean neighbours, yet endowed with greater economic and logistic liquidity, Nassau, The Bahamas’ capital city (on the island of New Providence), seemed the best venue for the first International Symposium on Composers of African & Afro-Caribbean Descent, held on February 21, 2013. New York-based orchestral conductor Marlon Daniel, with his Ensemble du Monde (in tow courtesy of the Nassau Music Society), and enterprising flutist Dr. Christine Gangelhoff, Assistant Professor of Music at the College of The Bahamas (where the symposium was held), built it; and they all came from the USA, Great Britain, Jamaica, Puerto Rico, Trinidad and The Bahamas.